Ontology development life cycle: a review - Mohd Rum, Siti Nurulain; Affendey, Lilly Suriani; Yaakob, Razali (Science & Engineering Research Support Society, 2019)
It is widely known that ontology plays a major role in semantic web as machine understandable language. There are manymethodologies have been developed in the last two decades. However, the degree of maturity and acceptance of these methodologies is still lacking due to the insufficient information about the techniques employed in them. Different methodologies provide different notions of development life cycle.Some methodologies can be manually created orsemi-automatically created. Some methodologies areapplication-driven orapplication independent. Some methodologies followan iterative development life cycle and some are not.Their application in real project is comparatively limited despites of their growing number. This study presents the similarities and differences of some prominent methodologies based on six phases of the ontology development life cycle, namelyscope definition, capturing, encoding, integration, evaluation and documentation.Another important aspect of ontology development is the ontology evolution. This topic is also presented in this paper